Comprehensive Evaluation of Satellite‐Based Precipitation at Sub‐Daily Time Scales Over a High‐Profile Watershed with Complex Terrain - Shuang Liu; Kaiheng Hu; Shaojie Zhang; Yujin Zeng (Earth and Space Science, 2019)
Abstract In this study, a preliminary quantitative evaluation of global precipitation measurement (GPM) mission precipitation products at sub‐daily time scales was performed in a typical and small watershed with complex terrain in southwestern China. The world heritage Jiuzhaigou Valley, which has been affected by many rainfall‐triggered debris‐flow disasters after the Ms 7.0 earthquake on 8 August 2017, was selected as the study area. The “early”, “late” and “final” half‐hourly GPM precipitations and hourly observations by four rainfall stations were used, and various indicators (general statistical indices, classification indicators, and a joint probability distribution function) were adopted as metrics to evaluate the GPM rainfall. Results indicated that the early and late hourly products showed a medium degree of correlation with ground observations, while the final hourly product showed better performances and may be used for research‐level applications in the study area. GPM products could approximately reproduce the diurnal cycles of observed precipitation whereas the relationship between peak rainfall and duration spell was in good agreement with ground observations. The 1‐hour final product was unable to significantly reduce the rate of missing report for rain although it was calibrated by global monthly data. An event‐based evaluation showed that the GPM performed well for the cumulative rainfall. The assessment results support the development of early‐warning models for rainfall‐triggered geological disasters, provide useful implications on the improvement of rainfall retrieval algorithm in complex mountainous areas, and may be used as reference for scientific studies in poorly sampled regions with similar geographical conditions as the Jiuzhaigou Valley.